Damping of subsynchronous resonance using a voltage source converter‐based high‐voltage direct‐current link in a series‐compensated Great Britain transmission network. Issue 3 (1st March 2014) - Livermore, Luke; Ugalde‐Loo, Carlos E.; Mu, Qing; Liang, Jun; Ekanayake, Janaka B.; Jenkins, Nick
Abstract : Owing to increased levels of generation in Scotland, substantial onshore and offshore reinforcements to the Great Britain (GB) transmission network have been proposed. Possible inland reinforcements include the use of series compensation through fixed capacitors. This potentially can lead to subsynchronous resonance (SSR). Offshore reinforcements are proposed by high‐voltage direct‐current (HVDC) links. In addition to its primary functions of bulk power transmission, a voltage source converter‐based HVDC link can be used to provide damping against SSR, and this function has been modelled. Simulation results have been carried out in Power Systems Computer‐Aided Design, with system analysis conducted in MATLAB. A real‐time hardware‐in‐the‐loop real‐time digital simulator‐HVDC test rig has been used to implement and validate the proposed damping scheme on an experimental platform. The simulation and experimental results show good agreement.